MOTIVASI MAHASISWA DALAM PEMBELAJARAN KIMIA - Amna Emda (Lantanida Journal, 2019)
Learning motivation was something that exists in an individual mind for doing something to achieve the goal. Motivation was needed to improve the cognitive abilities of each individual. In reality, there are still students at the Chemical Education Study Program who were less motivated to learn. This was characterized by active, discipline, task completion, the willingness of student to ask questions and solve problems in learning is still lacking. The aim of this study was to determine the level of motivation, influencing factors and efforts to increase student motivation in chemistry learning. The results showed that student's motivation in improving cognitive abilities on average was still low. The efforts were made by lecturers are to instil the values that can motivate the learning process, apply the better strategies and quality of teaching, approach individually or groups to improve the lecturer skills and apply the contextual based learning.